Circulating leptin levels are associated with physical activity or physical fitness in Japanese - Miyatake, Nobuyuki (Springer Japan, 2014)
OBJECTIVE: The aim of this study was to evaluate the link between circulating leptin levels and physical activity and/or physical fitness in apparently healthy Japanese. METHODS: A total of 85 men and 111 women who were not taking any medication were enrolled in this cross-sectional study. Circulating leptin levels, physical activity measured by tri-axial accelerometers and peak oxygen uptake were evaluated. We also assessed anthropometric data, blood pressure, blood examinations and energy intake. RESULTS: Circulating leptin levels were 3.2 ± 2.3 ng/mL in men and 5.9 ± 3.8 ng/mL in women. Circulating leptin levels were significantly and positively correlated with body weight, body mass index, abdominal circumference, insulin and the homeostasis model assessment index, and significantly and negatively correlated with peak oxygen uptake in both sexes. Stepwise multiple regression showed that peak oxygen uptake in men and physical activity evaluated by [Formula: see text] in women were determinant factors for circulating leptin levels after adjusting for confounding factors.